PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY UNTUK MENINGKATKAN SIKAP ILMIAH SISWA KELAS XI SMA N 9 PEKANBARU DALAM PEMBELAJARAN FISIKA - Yorsi Salfutri; M. Rahmad '; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrck: This research aims to determine the increasing and differenes in scientific attitude students by applying the guided discovery learning model and conventional in learning physics class XI SMA N 9 pekanbaru. The population of this research is class XI consisting of 4 classes. Samples taken are 2 classes, determination technique experimental class and control class are by simple random sampling. This research was conducted in SMA N 9 Pekanbaru from September to November 2015. This research is Quasi Experimental Design forms Nonequivalent Control Group Design. Instrument of collecting data in this research is a questionnaire scientific attitude students is given before and after learning. The indicators contained in the questionnaire that is honesty, coriosity, logical thinking, and accuracy. Data were analyzed by descriptive and inferential. Descriptive analysis of scientific attitude students to apply the guided discovery learning model has incrased, the values before learning is 3.89, after learning is 4.42, so the guided discovery learning model effectively applied to improve the scientific attitude students. The results of inferential analysis obtained by value thitung > ttabel ( 2,930 > 2,002 ) , then H0 is rejected so we can conclude there is a significant difference to the scientific attitude students in learning physics in class XI SMA N 9 Pekanbaru applying learning models guided discovery with a class that implements conventional teaching with a 95% confidence level .Key Words: Scientific Attitude, Guided Discovery, spring fore